2007
DOI: 10.1021/bm061155n
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate-Induced Degradation of Poly(3-hydroxybutyrate)s

Abstract: This communication shows that thermal degradation of poly(3-hydroxybutyrate)s (PHBs) is induced by carboxylate groups via a newly proposed E1cB mechanism. In PHBs with end groups in the form of carboxylic acid salts with Na+, K+, and Bu4N+ counterions, the proposed mechanism explains the dependence of thermal stability on the size of the counterion. The degradation via intermolecular alpha-deprotonation by carboxylate is suggested to be the main PHB decomposition pathway at moderate temperatures. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 17 publications
2
77
0
Order By: Relevance
“…The degradation products were analyzed by 1 H-NMR. Figure 5 depicts the spectra of volatile fraction produced during the first degradation stage, in the range of 120 to 270°C, and it shows appreciable quantities of crotonic acid, which is well known to be one of the main degradation products of PBL, together with low molecular weight fractions of the (R,S)-PBL having crotonyl end groups [28,[42][43][44][45]. Additionally, the NMR spectra of the solid residue were identical to the PCL homopolymer ( Figure 6).…”
Section: Thermal Properties Of the Obtained Copolymers 331 Thermogmentioning
confidence: 91%
“…The degradation products were analyzed by 1 H-NMR. Figure 5 depicts the spectra of volatile fraction produced during the first degradation stage, in the range of 120 to 270°C, and it shows appreciable quantities of crotonic acid, which is well known to be one of the main degradation products of PBL, together with low molecular weight fractions of the (R,S)-PBL having crotonyl end groups [28,[42][43][44][45]. Additionally, the NMR spectra of the solid residue were identical to the PCL homopolymer ( Figure 6).…”
Section: Thermal Properties Of the Obtained Copolymers 331 Thermogmentioning
confidence: 91%
“…This enhancement was explained as being due to the Lewis acidity of Ca 2+ and Mg 2+ facilitating the formation of a double bond by the elimination of -hydrogen. Kawalec et al (Kawalec et al, 2007) also reported on the enhancement of the thermal degradation of PHB by Na + , K + , and Bu 4 N + counter cations at chain-ends, proposing an E1cB mechanism. However, there was no discussion on the selectivity of pyrolyzates.…”
Section: Effects Of Alkali Earth Compounds As Depolymerization Catalystsmentioning
confidence: 96%
“…Several thermoanalytical procedures have been used to investigate the thermal degradation behavior of PHB, including thermogravimetry (TG) for the analysis of weight loss behavior (Kopinke et al, 1999;Galego & Rozsa, 1999;Li et al, 2001;He et al, 2001;Lee et al, 2001;Aoyagi et al, 2002;Carrasco et al, 2006;Kim et al, 2006;Kawalec et al, 2007;Liu et al, 2009;Ariffin et al, 2008Ariffin et al, , 2010, differential scanning calorimetry (DSC) for monitoring the heat of reaction (Kopinke et al, 1996), fast atom bombardment mass spectrometry (FAB-MS) (Ballistreri et al, 1989), electrospray ionization mass spectrometry (ESI-MS) (Kawalec et al, 2007), pyrolysis-mass spectrometry (Py-MS) (Abate, 1994;Kopinke et al, 1996), pyrolysisgas chromatography (Py-GC) (Lehrle, 1994), pyrolysis-GC/mass spectrometry (Py-GC/MS) (Kopinke et al, 1996(Kopinke et al, , 1997Aoyagi et al, 2002;Ariffin et al, 2008Ariffin et al, , 2010, TG/Fourier transform infrared spectroscopy (TG/FTIR) (Li et al, 2003), NMR (Melchiors et al, 1996;Kopinke et al, 1996;Ariffin et al, 2009), and pyrolysis-GC/FTIR (Li et al, 2003;Gonzalez et al, 2005), for the analysis of volatile products, and size exclusion chromatography (SEC) (Grassie et al, 1984;Kunioka & Doi, 1990;Nguyen et al, 2002;Kim et al, 2006) for the analysis of changes in molecular weight of residual PHB. (Kopinke et al, 1996;Galego & Rozsa, 1999;Li et al, 2001;…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of unsaturated (crotonate) end-groups in b-butyrolactone polymerisation was previously reported. These end-groups can be formed either in the initiation process or during propagation through a chain-transfer reaction to the monomer and through the recently reported E1cB intermolecular carboxylate-induced a-deprotonation mechanism of poly(3-hydroxyalkanoate)s. 60,61 Moreover, small amounts of oligomers with acetate end-groups have also been detected. The acetate end-groups were present in the original (R,S)-PHB sample with a high-molar mass and are derived from the initiator used during the preparation of this polymer sample.…”
Section: F I G 5 -Esi-ms/ms Fragmentation Experiments For the Ion Amentioning
confidence: 99%